Impact of soil types and root exudates on cadmium and petroleum hydrocarbon phytoremediation by Sorghum sudanense, Festuca arundinace, and Lolium perenne - He, Mengfan; Li, Zhongbao; Chen, Cheng; Mei, Ping (Frontiers in Ecology and Evolution, 2022)
Abstract: With the development of industrialization, soils around the world have been polluted by heavy metals and oil to different degrees in recent years, and soil remediation has become a global problem. Phytoremediation has a wide application prospect because of its environmental friendliness and easy availability of materials.【Objective】To explore the effects of soil types and root exudates on the removal of cadmium and petroleum hydrocarbon in soils.【Method】A pot experiments with three soil types (sandy, loamy and clayey) of the Changning-Weiyuan area of Sichuan province and three root exudates (citric acid, glycine, and maltose) were carried out using Sorghum sudanense (Piper) Stapf., Lolium perenne L., and Festuca arundinacea L. as test materials. Plants were grown in soils contaminated by cadmium and petroleum at different concentrations. 【Result】The biomass of S. sudanense, the translocation ratio and removal rate of cadmium in S. sudanense decreased gradually with increasing soil cadmium concentration. The promotion effects of the three root exudates on S. sudanense were in the following order: citric acid > glycine > maltose. At the same cadmium pollution conditions, the biomass levels of S. sudanense in sandy, loamy, and clayey soils were in the following order: clayey soil > loamy soil > sandy soil. On the contrary, the concentration, translocation ratio, and removal rate of cadmium in S. sudanense grown in the different soils treated with root exudates were in the following order: sandy soil > loamy soil > clayey soil. Under the three soil conditions, the fresh weight of F. arundinacea (0.36~0.68 g) and S. sudanense (0.51~0.99 g) increased significantly (p<0.05). The total petroleum hydrocarbons degradation efficiencies of F. arundinacea, L. perenne, and S. sudanense were high in sandy soil (34.27%~60.52%). Changing the type of root exudate had a significant impact on the degradation of total petroleum hydrocarbons in sandy soil (p<0.05).【Conclusion】This study showed that soil types impacted the accumulation of cadmium and petroleum in plants. Phytoremediation of cadmium and petroleum contaminated soil could be enhanced by the application of root exudates. This study recommend that the method is suitable for field remediation of soils contaminated with mild cadmium and petroleum hydrocarbons.